2018
DOI: 10.1080/15384047.2017.1394551
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c-3p inhibits cell migration and invasion of clear cell renal cell carcinoma via regulating SLC6A1

Abstract: In this study, we investigated the mechanism of miR-200c-3p and SLC6A1 in regulating cell activity of clear cell renal cell carcinoma (CCRCC). The mRNA and miRNA expressions of tissue specimens were analyzed by CapitalBio Corporation (Beijing, China). The expression of SLC6A1 in CCRCC cells was examined through qRT-PCR and western blot. The migration and invasion ability of 786-O cells was testified by transwell assay after transfected. 786-O cell proliferation ability was detected by MTT assay. Dual luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Using the miRNA target prediction algorithm TargetScan (http://www.targetscan.org), we determined that HMGB3 was a predicted target of miR‐200b‐3p and miR‐200c‐3p (Figure A). Crucially, both miR‐200b‐3p and miR‐200c‐3p have been shown to act as tumour suppressors during cancer development . In order to confirm the TargetScan prediction, we performed luciferase assays by cotransfecting miR‐200b‐3p and miR‐200c‐3p with wild‐type or mutated 3′‐UTR of HMGB3 into HEK293 cells (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the miRNA target prediction algorithm TargetScan (http://www.targetscan.org), we determined that HMGB3 was a predicted target of miR‐200b‐3p and miR‐200c‐3p (Figure A). Crucially, both miR‐200b‐3p and miR‐200c‐3p have been shown to act as tumour suppressors during cancer development . In order to confirm the TargetScan prediction, we performed luciferase assays by cotransfecting miR‐200b‐3p and miR‐200c‐3p with wild‐type or mutated 3′‐UTR of HMGB3 into HEK293 cells (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, both miR-200b-3p and miR-200c-3p have been shown to act as tumour suppressors during cancer development. 27,28 In order to confirm the TargetScan prediction, we performed luciferase assays by cotransfecting miR-200b-3p and miR-200c-3p with wild-type or mutated 3′-UTR of HMGB3 into HEK293 cells ( Figure 5B). Luciferase activity driven by the 3′-UTR of HMGB3 was significantly decreased in the presence of miR-200b-3p and miR-200c-3p ( Figure 5C).…”
Section: Hmgb3 Is Targeted By Mir-200b-3p and Mir-200c-3pmentioning
confidence: 99%
“…miRNAs are known to be an integral component of cancer development [17][18][19]. Several studies have highlighted the role of miR-182-5p in the development of different cancers [13,14].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…MiRNAs have essential biological roles and clinical implication in CCRCC [33]. MiR-200c-3p was shown to restrain CCRCC cell migration and invasion by targeting Solute Carrier Family 6 Member 1 (SLC6A1) [34], and miR-122 acted as a tumor promoter of CCRCC via down-regulating Forked-box class O3 (FOXO3) [35]. Herein, we found that miR-1233 directly targeted ACAT2 to be a pro-cancer molecule of CCRCC.…”
Section: Discussionmentioning
confidence: 94%